Synthesis, Potentiometric Titrations and Antioxidant Activities of Some 4-Acylamino-4,5-dihydro-1H-1,2,4-triazol-5-one Derivatives - Ynksek, Haydar; Alkan, Muzaffer; Islamoglu, Fatih; Bahteci, Sule; Elmastas, Mahfuz; Calapoglu, Mustafa; Ozdemir, Mustafa (Asian Journal of Chemistry, 2010)
Five novel 3-alkyl-4-cinnamoylamino-4,5-dihydro-1H- 1,2,4-triazol-5-ones (2) were synthesized by the reactions of 3-alkyl-4-amino-4,5-dihydro-1H-1,2,4-triazol-5-ones (1) with cinnamoyl chloride and characterized by elemental analyses and IR, 1H NMR, 13C NMR and UV spectral data. The newly synthesized compounds 2 were titrated potentiometrically with tetrabutylammonium hydroxide in four non-aqueous solvents such as isopropyl alcohol, t-butyl alcohol, acetonitrile and N,N-dimethylformamide and the half-neutralization potential values and the corresponding pKa values were determined for all cases. In addition, these new compounds (except compound 2a) and five recently reported 3-alkyl-4- isobutyrylamino-4,5-dihydro-1H-1,2,4-triazol-5-ones (3) were screened for their antioxidant activities.